Localising and tailoring research evidence helps public health decision making. (29th May 2018) - van der Graaf, Peter; Cheetham, Mandy; McCabe, Karen; Rushmer, Rosemary
Abstract: Background: Published research evidence is typically not readily applicable to practice but needs to be actively mobilised. Objectives: This paper explores the mechanisms used by information professionals with a specific knowledge mobilisation role to make evidence useful for local decision making and planning of public health interventions. Methods: Data are drawn from a NIHR project that studied how, when, where and by whom published research evidence is used in commissioning and planning across two sites (one in England and one in Scotland). Data included 11 in‐depth interviews with information professionals, observations at meetings and documentary analysis. Results: Published research evidence is made fit for local commissioning and planning purposes by information professionals through two mechanisms. They localise evidence (relate evidence to local context and needs) and tailor it (present actionable messages). Discussion: Knowledge mobilisation roles of information professionals are not recognised and researched. Information professionals contribute to the 'inform' and 'relational' functions of knowledge mobilisation; however, they are less involved in improving the institutional environment for sustainable knowledge sharing. Conclusion: Information professionals are instrumental in shaping what evidence enters local decision making processes. Identifying and supporting knowledge mobilisation roles within health libraries should be the focus of future research and training.